Cardiac Abnormalities in First-Degree Relatives of Unexplained Cardiac Arrest Victims: A Report From the Cardiac Arrest Survivors With Preserved Ejection Fraction Registry. (September 2016) - Steinberg, Christian; Padfield, Gareth J.; Champagne, Jean; Sanatani, Shubhayan; Angaran, Paul; Andrade, Jason G.; Roberts, Jason D.; Healey, Jeffrey S.; Chauhan, Vijay S.; Birnie, David H.; Janzen, Mikyla; Gerull, Brenda; et al.
Abstract : Background—: Unexplained cardiac arrest (UCA) may be explained by inherited arrhythmia syndromes. The Cardiac Arrest Survivors With Preserved Ejection Fraction Registry prospectively assessed first-degree relatives of UCA or sudden unexplained death victims to screen for cardiac abnormalities. Methods and Results—: Around 398 first-degree family members (186 UCA, 212 sudden unexplained death victims' relatives; mean age, 44±17 years) underwent extensive cardiac workup, including ECG, signal averaged ECG, exercise testing, cardiac imaging, Holter-monitoring, and selective provocative drug testing with epinephrine or procainamide. Genetic testing was performed when a mutation was identified in the UCA survivor or when the diagnostic workup revealed a phenotype suggestive of a specific inherited arrhythmia syndrome. The diagnostic strength was classified as definite, probable, or possible based on previously published definitions. Cardiac abnormalities were detected in 120 of 398 patients (30.2%) with 67 of 398 having a definite or probable diagnosis (17%), including Long-QT syndrome (13%), catecholaminergic polymorphic ventricular tachycardia (4%), arrhythmogenic right ventricular cardiomyopathy (4%), and Brugada syndrome (3%). The detection yield was similar for family members of UCA and sudden unexplained death victims (31% versus 27%; P =0.59). Genetic testing was performed more often in family members of UCA patients (29% versus 20%; P =0.03). Disease-causing mutations were identified in 20 of 398 relatives (5%). The most common pathogenic mutations were RyR2 (2%), SCN5A (1%), and KNCQ1 (0.8%). Conclusions—: Cardiac screening revealed abnormalities in 30% of first-degree relatives of UCA or sudden unexplained death victims, with a clear working diagnosis in 17%. Long-QT, arrhythmogenic right ventricular cardiomyopathy, and catecholaminergic polymorphic ventricular tachycardia were the most common diagnoses. Systematic cascade screening and genetic testing in asymptomatic individuals will lead to preventive lifestyle and medical interventions with potential to prevent sudden cardiac death. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00292032. Abstract : Supplemental Digital Content is available in the text.